Community Evaluation on The Effects of Tourism in Doot Poktoy, Lanuza - mariae khrisna baring arreza; James Garcia Esguerra (Journal of Business on Hospitality and Tourism, 2021)
Doot Poktoy is an emerging surfing destination in Mindanao. In developing tourism, Policymakers could aim for long-term tourism growth. Sustainable tourism is intensely dependent on the host community's support, view, and contribution to tourism programs; this safeguards the community and diminishes any adverse effects that can harm the environment and culture. However, literature is scarce about comparing the positive and negative effects of tourism.  Thus, this paper focuses on the following objectives: Determine the positive and negative effects of tourism and; Test the significant difference between the positive and negative responses. The study gathered 93 responses from Doot Poktoy residents'. It utilized the descriptive approach, with questionnaires indicating the agreement level in the values of tourism development: economic, socio-cultural, and environmental. The results revealed that the respondents had experienced both negative and positive effects of tourism and that they have a more negative view of tourism than a positive one.